Economic geographies of globalisation : a short introduction - Sokol, Martin (Edward Elgar, 2011)
This text provides a compact introduction to key theoretical approaches that help us to understand how economies work, why they suffer recessions and crises, and why economic inequalities at various levels are growing in the context of globalisation